Effects of Physical Activity Level, Strength, Balance, and Body Composition on Perceived Health in Healthy Adults - José Manuel Delfa-de-la-Morena; Pedro Pinheiro Paes; Frederico Camarotti Júnior; Débora Priscila Lima de Oliveira; Rubem Cordeiro Feitosa; Byanka Santos Cavalcante de Oliveira; Juan-José Mijarra-Murillo; Aranzazu Martínez Moya; Miriam García-González; Francisco De Asís-Fernández (Sports)
Background: Nowadays, not only is a high, long life expectancy desired, but also longevity with quality. Quality of life in adulthood is a multidimensional construct related to the perception of one’s own health, psychological and socio-emotional factors, functionality for daily activities, and body composition. Objective: This study evaluates the effects of physical activity level (PAL), strength, balance, and body composition on perceived health in healthy adults. Methods: An observational, cross-sectional study with consecutive, non-probabilistic inclusion of cases was conducted. Body fat percentage (BFP) was measured by DXA. Physical activity level was assessed using accelerometry. The strength index (S_Index) was estimated using dynamometry. Postural control was assessed through posturography. The composite equilibrium score from the Sensory Organization Test (SOT_CES) was conducted to measure postural stability under various sensory conditions using dynamic posturography. Perceived health was calculated using the SF36 questionnaire, which detects health states, both positive and negative. A linear regression model was generated between each domain of SF36 with SOT_CES, BFP, PAL, and S_Index. Results: A total of 64 males with a mean age of 55 ± 5 years and a mean body mass index of 27 ± 4 kg/m2 were recruited. Results showed a negative correlation between physical function (ß = −0.7; t = −3.163; p = 0.003; R2 = 23.7%) and general health (ß = −0.227; t = −3.425; p = 0.001; R2 = 17.4%) with BFP. Also, it showed a negative correlation between physical function (ß = 0.047; t = −2.643; p = 0.011; R2 = 17.5%) and general health (ß = 0.016; t = −3.044; p = 0.004; R2 = 14.6%) with S_Index. On the other hand, no relation was observed between SF36 and SOT_CES. Finally, only the emotional role showed a positive correlation (ß = −0.02; t = −2.629; p = 0.011; R2 = 23.1%) with PAL. Conclusion: A lower BFP and higher S_Index are associated with increased physical function and general health. Also, the higher the PAL, the greater the emotional health. On the other hand, no relation was observed between SF36 and the balance detected from SOT_CES.